The Processing of Global and Local Visual Information in Alzheimer’s Disease - Eriko Matsumoto; Yoshitaka Ohigashi; Misato Fujimori; Etsuro Mori (Behavioural Neurology)
We examined the quantitative and qualitative difference of the pattern with visuo-cognitive processing impairment in patients with early onset AD (EOAD) and late onset AD (LOAD). We use a visual attention task introduced by Navon (1977) to examine the function to integrate local visual stimuli into global image. Although the ability to identify solid digits ether of large and small size presented at the same exposure duration, EOAD performance was poor in the global perception especially at the short duration (20~msec). We provide evidence that this dysfunction is attribute to the AD pathology specific to early onset type.